The Effect of Integrated Entrepreneurship Development on the Performance of MSMEs in DKI Jakarta during the Pandemic Period - Krisnawati, Gita; Djamaluddin, Sartika (BASKARA : Journal of Business and Entrepreneurship, 2023)
The Jakpreneur Program is a Micro, Small, and Medium Enterprises (MSMEs) development program organized by the Jakarta Government, aimed at fostering entrepreneurship in MSMEs and facilitating MSME players. However, the Covid-19 pandemic has had a significant impact on Jakarta, with the highest number of Covid cases, resulting in increased unemployment and a rise in self-employed individuals. The objective of this study is to investigate the performance differences, measured by profit, between MSMEs that participate and do not participate in the Jakpreneur program, which includes training, marketing, and licensing, by considering internal factors. This study uses data from food sector MSMEs provided by the Jakarta Provincial Office of Food Security, Marine and Agriculture Agency in the years 2020, 2021, and 2022. The results of the regression data analysis using Ordinary Least Squares (OLS) show that in 2020 and 2021, the marketing and licensing programs have a significant positive influence on MSME profits, while in 2022, the training program has a significant positive influence on MSME profits. On internal factors, the number of workers, male gender and access to credit have a significant positive influence on MSME profits in all years.